2017
DOI: 10.21149/7851
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and adequacy of energy and nutrients in Mexican older adults: results from two National Health and Nutrition Surveys

Abstract: Quantile and logistic regression models were used to obtain medians and marginal effects of each nutrient, adjusting by confounders and survey design. Results. Dietary intake of energy and nutrients was similar in both surveys. Most common micronutrients at risk of dietary deficiency were, for vitamins: A, B-12, C, D and folate, and for minerals: calcium, iron and zinc, in both surveys. Excessive intake of sugar and saturated fat and low fiber intake were common. Conclusions. Diet in older Mexican adults is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
4
8
0
1
Order By: Relevance
“…Although it has been observed in many developed countries that women were more likely to engage in healthy living and healthy dietary choices [48, 49], studies conducted in developing countries as with our study generally reported better nutritional status among the males than females, likely because of the gender differences in social and economic aspects [15]. Lastly, it was observed that the prevalence of inadequate nutrient intake decreases as wealth status progresses, which was also observed in previous studies [50, 51]. However, increasing SES does not necessarily mean better nutritional status [52].…”
Section: Discussionsupporting
confidence: 87%
“…Although it has been observed in many developed countries that women were more likely to engage in healthy living and healthy dietary choices [48, 49], studies conducted in developing countries as with our study generally reported better nutritional status among the males than females, likely because of the gender differences in social and economic aspects [15]. Lastly, it was observed that the prevalence of inadequate nutrient intake decreases as wealth status progresses, which was also observed in previous studies [50, 51]. However, increasing SES does not necessarily mean better nutritional status [52].…”
Section: Discussionsupporting
confidence: 87%
“…The mean plasma vitamin D value found in the current study was closely similar to that reported by the Mexican Health and Aging Study (2012) in women over 60-years old [11]. Interestingly, the vitamin D levels in this study were lower than those determined in samples of the population also over 60 years old but living in the southern states of Mexico [67]. It is possible that this is due to a higher sun exposure in communities in the south part of Mexico which are much less urbanized than Mexico City, and possibly also to differences of lifestyle.…”
Section: Discussionsupporting
confidence: 89%
“…Oriental diet is rich in nuts, vegetables and fruits, decreasing the risk of cardiovascular and cognitive deterioration ( Dong et al, 2016 ). In contrast, the Mexican diet tends to be unhealthier with higher levels of cholesterol and saturated fat, less vegetables and fruit etc, leading to cerebrovascular risk factors such as high cholesterol, obesity, hypertension, diabetes, which becomes more pronounced with time ans leading to increased risk of cognitive decline ( Cruz-Góngora, Cuevas-Nasu, Flores-Aldana, & Shamah-Levy, 2017 ). A healthier diet is linked with those who are more physically active ( Woo, 2000 ).…”
Section: Discussionmentioning
confidence: 99%